Rerouting the metabolic pathway in Lactococcus lactis ATCC 11454 to improve nisin productivity by disrupting lactate dehydrogenase (ldh) - Mohd Rasid, Nur Hidayah; Abdul Halid, Nadrah; Ai-Lian, Adelene Song; Sabri, Suriana; Abd Rahim, Muhamad Hafiz; Saari, Nazamid; Hasan, Hanan (Taylor and Francis, 2024)
Nisin is an effective biopreservative, however its wide application in food is restricted due to its low productivity. Therefore, the present work aimed to increase its yield by disrupting lactate dehydrogenase (ldh) and re-directing the carbon flow towards nisin production. The ldh-deficient Lactococcus lactis ATCC 11454 (ldhΔ) strain was created by inserting ampicillin (amp) within the ldh to disrupt its function. Under controlled fermentation conditions (30°C, pH 6, 1.0% glucose), the ldhΔ strain exhibited negligible decrease in pH (2.5%) over 48 h, in contrast to the wild-type (WT) strain, which experienced a 23.6% decrease in pH (pH 4.2). Overall, the ldhΔ strain showed a significant (p < 0.05) increase in growth and nisin activity by 24.9% and 62% compared to the WT strain, respectively. This strategy could serve as a practical approach to further enhance the production of bacteriocin or other compounds by modulating their metabolic pathways.